Recent Insights Into the Prognostic and Therapeutic Applications of Lysozymes - Jiang, Lin; Li, Yunhe; Wang, Liye; Guo, Jian; Liu, Wei; Meng, Guixian; Zhang, Lei; Li, Miao; Cong, Lina; Sun, Meiyan (Frontiers in Pharmacology, 2021)
Lysozymes are naturally occurring enzymes present in a variety of biological organisms, such as bacteria, fungi, and animal bodily secretions and tissues. It is well known that lysozymes and lysozyme-like enzymes can be used as antibacterial agents, as well as inhibit fungi, yeasts, and viruses. Lysozyme is also an important component of the innate immune system in most mammals. In recent years, more evidence has shown the immune-modulatory effects of lysozymes against infection and inflammation. In addition, recent studies revealed the anti-cancer activities of lysozyme in multiple types of tumors, potentially through its immune-modulatory activities. The levels of lysozyme are associated with cancers and other diseases. This review summarized the major features and mechanisms of lysozymes highlighting the prognostic and therapeutic applications and recent advances of lysozymes in cancers, hypertension, and viral diseases.